Estimation of thermal contact conductance value between boron steel blank and tool surface at different value of applied pressure in hot stamping process - Mohd Ali Hanafiah, Shaharudin (2014)
In hot stamping, one of the key factor for successful process control as well as producing a final part strength of more than 1500 MPa is the ability to control heat transfer from the blank throughout the process especially during quenching where the blank need to be cooled down rapidly to transform it’s microstructure into martensite phase. In order to control heat transfer process, a study need to be carried out for understanding the characteristics of heat transfer between two solid bodies in contact to each other and investigates the influence of applied pressure to the heat transfer as well as optimizing its. To do so, a systematic approach has been planned to analyze the heat transfer using finite element analysis (FEA) using commercial simulation software as well as the experimental work. The FEA is done by simulating the heated blank or the specimen cool down as it brought into contact to the tools which has a temperature slightly lower than ambient temperature. The effect of different values of applied pressure is simulates by manipulating the values of thermal contact conductance at the blank and tool surface in contact and the thermal contact conductance values will be simulates ranging in between 1000 to 2000 W/m2K. Meanwhile, the experiment being conducted to measure temperature changes of the blank and tool as it is compress in between a set of experimental tool (upper and lower tool) at different pressure ranging between 5 to 35 MPa. The experiment results will be used to compute the actual thermal contact conductance and compared with the FEA simulation. Based on these analyzed result from both approach, the influence of the applied pressure to the heat transfer between two solid bodies in contact as well as the optimum value of applied pressure possibly defined.